COVID-19 impact on e.commerce usage - Usas, Antanas (2021)
Online stores, ad portals, shopping apps have become part of everyday life in 2020-2021. The Covid-19 epidemic has rapidly forced numerous entities (public, business, and private) to become predominantly oriented to electronic commerce in the last few months (Pejić-Bach, 2021). Business in the online space faces new challenges that require additional knowledge and skills.  The object of the research is the assessment how covid-19 impact on ecommerce usage in Lithuania. The aim of the work is to examine ecommerce usage in Lithuania during covid-19 pandemic. Methods: scientific literature analysis, statistical data analysis.  Businesses had to offer a wider range of services in order to survive. The issue of cybersecurity has grown. Consumers have also reacted ambiguously to this situation. Not only are economic factors that determine the frequency or quantity of consumer purchases distinguished, but also social and psychological factors, such as loss of motivation or apathy. The vast majority of Lithuanian shoppers were selling local online shops. The amount of money spent on online shopping has also increased. The pandemic has increased the scope of ecommerce and the range of services in Lithuania despite the deteriorating economic and social situation.